Towards an overdetermined design for informal high school girls’ learning in geospatial technologies for climate change - Solís, Patricia; Huynh, Niem Tu; Huot, Philippe; Zeballos, Marcela; Ng, Astrid; Menkiti, Nwasinachi (International Research in Geographical and Environmental Education, 2019)
This article explores an experimental effort to develop a short-term informal learning experience to achieve awareness, confidence and knowledge in geography and geospatial technologies related to environmental and climate change for all participants but particularly for female secondary learners. The intervention incorporated various elements to promote gender-sensitive technical and cultural literacy through an international outreach and science diplomacy framework, justified by various kind of literature in STEM learning. We recount the experiences of three cohorts of students learning about impacts of climate change at sites in Bolivia, South Africa and Panama. The results of student surveys before, immediately after, and 9 months post-participation reveal the extent to which the design met objectives for learning, across genders. Our experimental conclusion reinforces the idea that even short-term, informal learning programs can elicit greater confidence, knowledge and abilities in all students, especially female students, when as many as possible of the elements known to improve gendered participation for STEM are taken into consideration into the very design of the experience. We coin the term “overdetermined design” to designate this kind of approach to take reinforcing, even redundant steps to increase the likelihood of obtaining desired results of improved confidence overall and reducing the gender gap, particularly through the use of geospatial technologies.
Keywords: GIS; Gender; climate change; international exchange; secondary school; technology